The Disruption of Memory Consolidation of Duration Introduces Noise While Lengthening the Long-Term Memory Representation of Time in Humans - Derouet, Joffrey; Doyère, Valérie; Droit-Volet, Sylvie (Frontiers in Psychology, 2019)
This study examined the effect of an interference task on the consolidation of duration in long-term memory. In a temporal generalization task, the participants performed a learning phase with a reference duration that either was, or was not, followed 30 minutes later by a 15-min interference task. They were then given a memory test, 24h later. Using different participant groups, several reference durations were examined, from several hundred milliseconds (600ms) to several seconds (2.5, 4 and 8s). The results showed that the scalar timing property (i.e. precision proportional to judged duration) was preserved despite the interference task given during the memory consolidation process. However, the interference task increased the variability of time judgment and tended to produce a lengthening effect in all reference duration conditions. The modeling of individual data with parameters derived from scalar expectancy theory suggests that disrupting the memory consolidation of learned reference durations introduces noise in their representation in memory, with time being specifically distorted towards a lengthened duration.